PENGARUH PEMERIKSAAN BAGASI KABIN TERHADAP KEPUASAN PENUMPANG MASKAPAI CITILINK INDONESIA DI BANDAR UDARA INTERNASIONAL YOGYAKARTA - Nadiya Puji Oktaningrum; Irwina Meilani (CV. ADIBA AISHA AMIRA, 2024)
Inspection of passenger cabin baggage is an inspection carried out by gate officers to confirm whether or not the luggage carried by passengers is in line with the applicable rules and regulations, this inspection is carried out in terms of weight and size of luggage. If it is not appropriate, a paid baggage sweeping will be applied at a cost borne by the passenger which is then entered and counted into the cargo compartment. With the application of paid baggage sweeping, it can affect passenger perceptions and satisfaction in using Citilink Indonesia airlines, but this is done as a preventive effort in realizing flight security, comfort and safety. The purpose of this study is to determine how much influence the inspection of passenger cabin baggage carried out by Citilink Indonesia airlines has on passenger satisfaction. This study uses quantitative methods with an associative research approach, sampling using non probability sampling with purposive sampling technique. Data collection uses a questionnaire method with data analysis techniques, namely validity, reliability and hypothesis testing. The study results show that H0 is rejected and Ha is accepted, which shows that there is a significant influence between cabin baggage inspection and passenger satisfaction from Citilink Indonesia airlines, especially at Yogyakarta International Airport where the tcount value is 3.739> ttable 0.201 and a significance value of 0.002 <0.05. Passengers who have experienced paid baggage sweeping indicate unsatisfactory results for passengers as indicated by the level of passenger satisfaction with a coefficient of determination value of 12.9%. This value indicates other factors outside the cabin baggage inspection process that have an impact on passenger satisfaction. Some of the causes vary such as lack of information about paid baggage sweeping information at the boarding gate and passenger understanding of paid baggage sweeping regulations.